Luxury and public happiness political economy in the Italian Enlightenment - Wahnbaeck, Till (Oxford historical monographs., 2004)
This work charts the development of political economy in 18th-century Italy, arguing that the focus on economic thought is characteristic of the Italian Enlightenment at large. Through an analysis of the debate about luxury, it traces the shaping of a new language of political economy.